Determination of the Phenolic Composition and Antioxidant Activity of Pear Extracts - Mindaugas Liaudanskas; Kristina Zymonė; Jonas Viškelis; Almantas Klevinskas; Valdimaras Janulis (Journal of Chemistry)
The specific HPLC analytical procedure was developed and validated for the determination of phenolic compounds in pear samples of different popular cultivars “Conference,” “Concordia,” “Grabova,” and “Patten.” HPLC mobile phase consisted of 0.05% (v/v) trifluoroacetic acid in water and 100% (v/v) acetonitrile. The HPLC method was used to identify and confirm the specificity of 8 analytes: chlorogenic acid, rutin, hyperoside, isoquercitrin, isorhamnetin rutinoside, quercitrin, quercitrin malonyl glucoside, and isorhamnetin glucoside. Repeatability % RSD did not exceed 3.87%, and intermediate precision did not exceed 4.63%. The total content of phenolic compounds varied from 0.51±0.001 mg/g (cv. “Concordia”) to 1.11±0.013 mg/g (cv. “Patten”). Chlorogenic acid was the major component in all the tested pear cultivars. The highest amount of chlorogenic acid (0.69±0.033 mg/g) was found in pear samples of the cultivar “Grabova,” and the highest amount of flavonol compounds (1.11±0.013 mg/g) was found in pear samples of the cultivar “Concordia.”